Penerapan Model Pembelajaran Student Teams Achievement Division (STAD) dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Andi Milda Malia (IQRO: Journal of Islamic Education, 2019)
This study aims to to see the application of cooperative kind of classroom learning type student teams achievement division ( stad ) in improving the learning outcomes for islamic education a student of class viiib 7 palopo public junior high schools .This research is research the act of class .The research results show that the results of a: ( 1 ) student learning on the subjects of islamic education class VIIIB in public junior high schools 7 palopo before cooperative kind of classroom learning type student teams achievement division ( stad ) applied is currently far of the value of the criteria set minimum ketuntasan kkm, 78 .( 2 ) the application of cooperative kind of classroom learning on the subjects of islamic education class viiib in public junior high schools 7 palopo it was rarely applied by reason of the condition of class that does not support .( 3 ) the application of cooperative kind of classroom learning type student achievement division ( stad teams to improve learning outcomes for islamic education a student of class VIIIB public junior high schools 7. It is seen of student test scores in the cycle iii with grade point average 89,6.